Ultrahigh-hardness cavitation-erosion-resistant high-entropy alloy coating and preparation method thereof
By optimizing the atomic ratio of high-entropy alloys and using vacuum induction aerosol powdering and supersonic flame spraying technology, a high-entropy alloy coating with a single BCC phase was prepared, which solved the problem of insufficient hardness of existing coatings and achieved Extra high hardness and excellent cavitation resistance.
Patent Information
- Application Number
- CN202411689068.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing cavitation-resistant high-entropy alloy coatings are insufficient in hardness, making it difficult to maintain cavitation resistance under repeated impacts of high-pressure shock waves or high-speed microjets.
High entropy alloy coatings with a single BCC phase were prepared by optimizing the atomic ratio of Al, Cr, Co and Ni, combined with vacuum induction aerosol powdering and supersonic flame spraying.
The ultra-high hardness of the coating is achieved, with nanohardness reaching 9.1~11.4 GPa and microhardness reaching 858~881 HV0.1, significantly improving the cavitation resistance and even exceeding the traditional Cr3C2-NiCr cermet coating.
Smart Images

Figure CN119464998A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of advanced metal materials and surface protection, and specifically relates to an ultra-high hardness cavitation-resistant high-entropy alloy coating and a preparation method thereof. Background Art
[0002] Cavitation is the most common threat to the safe operation of flow-through components such as propellers or turbine blades working in a hydrodynamic environment. The damage caused by cavitation to materials mainly comes from the mechanical damage caused to the material surface by the high-pressure shock wave and high-speed micro-jet (cavitation load) generated by the collapse of cavitation bubbles. Therefore, finding high-strength and high-hardness materials has always been the research focus in the field of cavitation protection. Since cavitation starts from the surface of components, it is undoubtedly a more economical and practical way to coat the surface of flow-through components with materials with good cavitation resistance through advanced surface engineering technologies such as thermal spraying.
[0003] Metal ceramic coatings represented by WC-CoCr and Cr3C2-NiCr (Wear, 2016, 364-365, 201-210) are the earliest surface protective coatings applied on the surface of flow-passing parts because of their high hardness and good resistance to the impact of cavitation loads. However, the actual service life of these coatings is often significantly shorter than their initial design life. After research and analysis, people found that although the hard WC and Cr3C2 phases can resist the impact of cavitation loads, the bonding phase metal Co or NiCr alloy is first impacted and peeled off due to its low hardness, and then the WC or Cr3C2 particles without bonding will also peel off quickly under the action of the load. In addition, carbide phases such as WC and Cr3C2 are extremely sensitive to high temperature and oxygen. They are easily oxidized and decomposed in the process of preparing coatings using industrial technologies such as supersonic flame spraying or atmospheric plasma spraying, which significantly destroys the toughness of the coatings. Therefore, the cavitation protection ability of such coatings is still far from people's requirements.
[0004] Due to its own high entropy effect, lattice distortion effect, hysteresis diffusion effect and cocktail effect, high entropy alloys often show mechanical strength that is difficult to match with traditional metal materials, and tend to form a simple solid solution structure, so it has become a research hotspot for new cavitation protection coatings. The invention patent "A high entropy alloy coating resistant to cavitation-corrosion and its preparation method" with publication number CN115418595B discloses a high entropy alloy powder and coating based on face-centered cubic phase (FCC). The coating shows a high work hardening index and good ability to absorb impact energy, but its hardness is still low. Under the repeated impact of high-pressure shock waves or high-speed microjets, the surface layer will inevitably enrich structural defects such as dislocations due to plastic deformation, followed by fatigue delamination and accelerated cavitation damage (ACS Applied Materials&Interfaces, 2023, 15(2), 3651-3663).
[0005] To date, people have not yet developed a high-entropy alloy coating with a hardness close to that of a metal-ceramic coating and a uniform structure, resulting in limited practical applications of this type of coating. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a high-entropy alloy coating with ultra-high hardness and a preparation method thereof, which can not only obtain a spherical spraying powder with a single face-centered cubic structure (BCC) and a high-density coating through vacuum induction atomization powder making technology and supersonic flame spraying technology that are convenient for industrial production, but also has extremely high nanohardness (9.1-11.4 GPa) and microhardness (858-881 HV) without any post-processing process. 0.1 ), which is the maximum value of high entropy alloy coatings prepared by the same process reported in China, and even exceeds the Cr3C2-NiCr metal ceramic coating (780±40 HV 0.1 ) (Tribology Letters, 2010, 37, 463-475), thus showing excellent cavitation protection ability, and has great application potential as a cavitation-resistant coating on the surface of flow-through components such as turbines, propellers, and thrust bearings.
[0007] 1. Preparation of ultra-high hardness high entropy alloy coating A super-high hardness cavitation-resistant high-entropy alloy coating, which comprises the following components (at.%): Al 20%-26%, Cr 30%-34%, Co 30%-34%, and Ni 16%-22%.
[0008] The preparation method is as follows: (1) preparing pure metal raw materials containing Al, Cr, Co and Ni according to the atomic percentage of the high entropy alloy coating converted into mass percentage, cleaning the crucible at the same time, and then placing the prepared raw materials into the crucible of the induction heating furnace; (2) Evacuate the air to ensure that the vacuum degree is ≤1×10 -1 Pa, the raw material is heated to 1250~1750℃ through an induction coil to melt and flow into the atomization zone, and the metal liquid is impacted and broken by high-speed and high-pressure inert gas to atomize it into fine metal droplets, which are then cooled and solidified into high-entropy alloy powder in the atomization chamber. After screening, the powder with a particle size range of 15~70 μm suitable for supersonic flame spraying technology is obtained; (3) The surface of the metal substrate is roughened by sandblasting and cleaned, and then fixed on a spraying table. After setting the spraying process parameters, the supersonic flame spraying equipment is started, and the powder obtained in step (2) is sent into the flame flow for spraying and deposition on the surface of the metal substrate to obtain an ultra-high hardness cavitation-resistant high-entropy alloy coating.
[0009] In step (1), the purity of the pure metal raw materials of Al, Cr, Co and Ni is above 99.9 wt.%.
[0010] In step (2), the inert gas is any one of nitrogen, argon and helium, with a pressure of 0.5-5 MPa and a flow rate of 900-1500 m 3 / h.
[0011] In step (3), the metal substrate is one of copper alloy, titanium alloy, aluminum alloy, stainless steel, nickel aluminum bronze, manganese aluminum bronze, aluminum bronze, L907A steel, and cast steel, and the roughness of the metal substrate surface after sandblasting is Ra≥1 μm.
[0012] In step (3), the fuel gas used by the supersonic flame spraying equipment is natural gas, propane or aviation kerosene, the auxiliary fuel gas is oxygen or air, and the carrier gas is nitrogen, argon or helium.
[0013] The spraying parameters in step (3) are oxygen flow rate 50~56 m 3 / h, gas flow rate 20~25 L / h, powder feeder speed 20~25 rpm, spray gun moving speed 200~1000 mm / s, spraying distance 25~40 cm, stroke spacing 1~4mm, compressed air pressure 100~120MPa, compressed air flow rate 18~22 m 3 / h.
[0014] The thickness of the coating deposited in step (3) is 100-800 μm, and the phase structure is a single BCC phase.
[0015] 2. Morphology and structure of high entropy alloy powder Figure 1 The SEM image of the high entropy alloy powder of the present invention is given. It can be seen that the powder exhibits good sphericity and a smooth surface, indicating that the use of the optimized metal element formula system of the present invention, especially the optimized melting temperature and atomizing gas pressure and flow rate, is very suitable for producing spherical high entropy alloy powders through vacuum induction gas atomization industrial powder making technology, which is extremely beneficial for improving the fluidity of the powder. In addition, it can be seen from the figure that the particle size range of the powder is mainly distributed in 15~53μm, indicating that the high entropy alloy powder after screening is just in the particle size range most suitable for supersonic flame spraying technology.
[0016] Figure 2 The XRD spectrum of the high entropy alloy powder of the present invention is given. It is not difficult to find that the powder has only the diffraction peak of the BCC phase, without any other impurity peaks, indicating that the atomic ratio of Al, Cr, Co, and Ni optimized by the present invention does not cause element precipitation or heterogeneous nucleation due to the solubility interval and electronegativity difference between the four elements during the atomization powder making process. Although the content of the Al element is significantly higher than that of the high entropy alloys disclosed in CN115418595B, the simple solid solution phase can still remain stable, and a new type of high entropy alloy powder material with a phase structure significantly different from the previous single BCC phase is obtained. This is extremely beneficial for making full use of the strong lattice distortion and concentration fluctuation brought about by the atomic size and electronegativity difference between Al and the other three elements to significantly enhance the mechanical strength and load impact resistance of the high entropy alloy.
[0017] 3. Microstructure of high entropy alloy coating Figure 3 The SEM image of the polished cross section of the high entropy alloy coating of the present invention is given. It can be seen that the structure of the coating is very dense, and almost no pores are observed inside the coating. Moreover, the bonding between the coating and the metal substrate interface is also very tight, and there are no obvious defects, indicating that the powder feed composition, morphology and particle size range optimized by the present invention, especially the supersonic flame spraying process parameters, are very suitable for preparing highly bonded and dense high entropy alloy coatings, which are beneficial to its coating and use on the surfaces of various metal parts.
[0018] Figure 4 The XRD spectrum of the high entropy alloy coating of the present invention is given. It can be found that the coating still perfectly retains the single BCC phase crystal structure of its spray powder, and no diffraction peaks of other crystal structures, intermetallic compounds or oxides and other impurities appear, which once again proves that the optimized powder composition and supersonic flame spraying parameters of the present invention can effectively maintain the stability of the new solid solution during the high-temperature spraying process, which is very critical for ultimately obtaining a high entropy alloy coating with ultra-high strength and excellent cavitation resistance.
[0019] 4. Performance test of high entropy alloy coating In order to better study the performance of the high entropy alloy coating of the present invention, a series of tests on its mechanical properties were carried out using a nanoindenter and a microhardness tester. The results are as follows Figure 5 and 6 It can be seen that the nanohardness of the high entropy alloy coating of the present invention is as high as 9.1~11.4 GPa, and the microhardness is also 858~881 HV 0.1 These data are not only significantly higher than those of the Al 10 Cr 28 Co 28 Ni 34 The high entropy alloy coating is also higher than the traditional AlCrCoFeNi high entropy alloy coating with BCC phase as the main component prepared in Comparative Example 2, and even higher than the Cr3C2-NiCr metal ceramic coating (780±40 HV 0.1 ) (Tribology Letters, 2010, 37, 463-475). Among them, the FCC phase is mainly composed of Al 10 Cr 28 Co 28 Ni 34 The nanohardness and microhardness of the high entropy alloy coating are only 4.7 GPa and 516 HV respectively. 0.1 The nanohardness and microhardness of the AlCrCoFeNi high entropy alloy coating dominated by BCC phase are only 7.7 GPa and 705 HV respectively. 0.1 , which is about 10% to 60% lower than that of the high entropy alloy of the present invention. This shows that the present invention has successfully developed a new high entropy alloy coating with a single BCC phase that is comparable to the hardness of traditional metal ceramic coatings.
[0020] An ultrasonic vibration cavitation tester was used to conduct cavitation experiments on the high entropy alloy coating prepared by the present invention, the high entropy alloy coating prepared in Comparative Examples 1 and 2, and L907A steel, a common metal material for flow-through components, in deionized water in accordance with GB / T 6383-2009 standard. The test conditions were as follows: the temperature of the deionized water was (25±2)°C, the vibration frequency of the amplitude rod was 20 kHz, the amplitude was 50μm (peak-to-peak), the distance between the lower end of the amplitude rod and the coating surface was 0.5 mm, and the distance between the sample surface and the liquid surface was 12 mm. SEM was used to observe the surface SEM morphology of the high entropy alloy coating of the present invention and the high entropy alloy coating prepared in Comparative Example 1 after cavitation for 3 h. Figure 7 As shown in Figure 1, the cavitation damage of the coating surface material in Comparative Example 1 is more serious, while the peeling degree of the high entropy alloy coating surface of the present invention is much milder, indicating that the ultra-high hardness high entropy alloy coating of the present invention can better resist the mechanical impact caused by cavitation collapse and effectively prevent the peeling of the material. The cumulative mass loss of the sample after different cavitation times was weighed using a 1 / 10,000 balance. The results are shown in Figure 1. Figure 8 It is not difficult to find that after cavitation for 10 h, the cumulative mass loss of the high entropy alloy coatings prepared in Examples 1-3 are 6.6 mg, 7.2 mg and 6.9 mg respectively, which are significantly lower than metal ceramic coatings such as WC-CoCr and Cr3C2-NiCr (Wear, 2016, 364-365, 201-210); while the cumulative mass loss of the high entropy alloy coating in Comparative Example 1 is 11.2 mg, the cumulative mass loss of the high entropy alloy coating in Comparative Example 2 is 20.1 mg, and the cumulative mass loss of L907A steel is 69.7 mg, which is significantly higher than the coating of the present invention. It is proved that the ultra-high hardness high entropy alloy coating with a single BCC phase prepared by the present invention has extremely superior cavitation resistance, can produce more consistent deformation or resistance to deformation under cavitation load, avoids the situation where the selective destruction of individual phases accelerates the overall damage of the material, and is more suitable for use as an anti-cavitation coating than other existing metal or metal ceramic coatings.
[0021] In summary, the present invention has the following advantages compared with the prior art: The present invention optimizes the atomic ratio of the four metal components of Al, Cr, Co and Ni and the process parameters of vacuum induction gas atomization powder making and supersonic flame spraying, and can significantly increase the content of the Al element, which has obvious differences in atomic size, electronegativity and solubility from the other three elements, on the basis of ensuring the stability of the high-entropy solid solution structure, and greatly amplifies the strengthening effect brought about by the lattice distortion and concentration fluctuation caused by the component. Therefore, the coating exhibits a nanohardness of 9.1-11.4 GPa and a microhardness of 858-881 HV without any post-processing process. 0.1 The ultra-high hardness is not only the maximum value of the high-entropy alloy coating prepared by the same process reported in China, but even exceeds the Cr3C2-NiCr metal ceramic coating prepared by supersonic flame spraying technology, and can effectively resist the damage of external forces. More importantly, the high-entropy alloy system of the present invention can obtain spherical powder and dense coating of a single BCC phase through very mature industrial production technologies such as vacuum induction atomization powder making and supersonic flame spraying, and can effectively prevent the coating from selectively peeling off and damaging due to uneven physical phase structure under the impact of cavitation load, showing much better cavitation resistance than other existing metal or metal ceramic coatings, so it is very suitable for promotion and application on the surfaces of various complex and special-shaped flow-through parts such as turbines, propellers, thrust bearings, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the SEM morphology of the high entropy alloy powder of Example 1 of the present invention.
[0023] Figure 2 This is the XRD spectrum of the high entropy alloy powder of Example 1 of the present invention.
[0024] Figure 3 This is the SEM cross-sectional morphology of the high entropy alloy coating of Example 1 of the present invention.
[0025] Figure 4 This is the XRD spectrum of the high entropy alloy coating of Example 1 of the present invention.
[0026] Figure 5 Nanohardness of the high entropy alloy coatings of the embodiments of the present invention and the comparative example.
[0027] Figure 6 The microhardness of the high entropy alloy coatings of the embodiments of the present invention and the comparative example.
[0028] Figure 7 The surface SEM morphologies of the high entropy alloy coatings of Example 1 of the present invention and Comparative Example 1 after cavitation in deionized water for 3 h.
[0029] Figure 8 The cavitation cumulative mass loss curves of the high entropy alloy coating of the embodiment of the present invention and the comparative example and L907A steel in deionized water. DETAILED DESCRIPTION
[0030] The present invention is further explained below with reference to specific embodiments.
[0031] Example 1 (1) Select pure metals of Al, Cr, Co and Ni with a purity of more than 99.9 wt.% as raw materials, and mix them according to the atomic percentage: Al 22%; Cr 30%; Co 30%; Ni 18%. Before mixing, remove the oxide film and impurities on the surface of the raw materials. When mixing, convert the atomic ratio into the percentage of the mass of each element in the total mass, weigh them, and put them into the crucible.
[0032] (2) Place the crucible into the vacuum induction atomization furnace, cover the furnace door, and start evacuating until the vacuum reaches 5×10 -2 After Pa, the raw materials in the crucible are heated to 1400~1600 ℃ through the induction coil to melt, and the molten metal flows into the atomizing nozzle through the guide hole.
[0033] (3) Use argon gas at a pressure of 1-2 MPa at 800-1500 m 3 The flow rate of / h is through the atomizing nozzle to impact and break the molten metal falling into the atomization area, so that it is atomized into fine metal droplets, which are then cooled and solidified in the atomization chamber to form high entropy alloy powder. After screening, spherical Al2O3 with a particle size range of 15~53 μm is obtained. 22 Cr 30 Co 30 Ni 18 powder.
[0034] (4) Al was sprayed and deposited on the surface of the 316L stainless steel substrate after sandblasting by using supersonic flame spraying technology. 22 Cr 30 Co 30 Ni 18 The corresponding coating material can be obtained by high entropy alloy powder. The spraying process is oxygen flow rate 52.3 m 3 / h, kerosene flow rate 22.7 L / h, powder feeder speed 21 rpm, spray gun moving speed 600 mm / s, spraying distance 38.0 cm, pass spacing 2 mm, compressed air pressure 110 MPa, compressed air flow rate 19 m 3 / h, the coating thickness is about 320 μm.
[0035] (5) Phase structure and properties of high entropy alloy coating: The crystal structure is a single BCC phase, the nanohardness is 11.4 GPa, and the microhardness is 881 HV 0.1 The cumulative mass loss after cavitation in deionized water for 10 h is only 6.6 mg, showing the characteristics of typical ultra-high hardness and extremely excellent anti-cavitation performance.
[0036] Example 2 (1) Select pure metals of Al, Cr, Co and Ni with a purity of more than 99.9 wt.% as raw materials, and mix them according to the atomic percentage: Al 22%; Cr 30%; Co 30%; Ni 18%. Before mixing, remove the oxide film and impurities on the surface of the raw materials. When mixing, convert the atomic ratio into the percentage of the mass of each element in the total mass, weigh them, and put them into the crucible.
[0037] (2) Place the crucible into the vacuum induction atomization furnace, cover the furnace door, and start evacuating until the vacuum reaches 5×10 -2 After Pa, the raw materials in the crucible are heated to 1400~1600 ℃ through the induction coil to melt, and the molten metal flows into the atomizing nozzle through the guide hole.
[0038] (3) Use argon gas at a pressure of 1-2 MPa at 800-1500 m 3 The flow rate of / h is through the atomizing nozzle to impact and break the molten metal falling into the atomization area, so that it is atomized into fine metal droplets, which are then cooled and solidified in the atomization chamber to form high entropy alloy powder. After screening, spherical Al2O3 with a particle size range of 15~53 μm is obtained. 22 Cr 30 Co 30 Ni 18 powder.
[0039] (4) Using supersonic flame spraying technology to spray and deposit Al on the surface of the nickel-aluminum bronze substrate after sandblasting roughening 22 Cr 30 Co 30 Ni 18 The corresponding coating material can be obtained by high entropy alloy powder. The spraying process is oxygen flow rate 54.5 m 3 / h, kerosene flow rate 23.4 L / h, powder feeder speed 23 rpm, spray gun moving speed 500 mm / s, spraying distance 38.0 cm, pass spacing 2 mm, compressed air pressure 110 MPa, compressed air flow rate 19 m 3 / h, the coating thickness is about 450 μm.
[0040] (5) Phase structure and properties of high entropy alloy coating: The crystal structure is a single BCC phase, the nanohardness is 9.7 GPa, and the microhardness is 858 HV 0.1 The cumulative mass loss after cavitation in deionized water for 10 h is only 7.2 mg, showing the characteristics of typical ultra-high hardness and extremely excellent anti-cavitation performance.
[0041] Example 3 (1) Select pure metals of Al, Cr, Co and Ni with a purity of more than 99.9 wt.% as raw materials, and mix them according to the atomic percentage: Al 22%; Cr 30%; Co 30%; Ni 18%. Before mixing, remove the oxide film and impurities on the surface of the raw materials. When mixing, convert the atomic ratio into the percentage of the mass of each element in the total mass, weigh them, and put them into the crucible.
[0042] (2) Place the crucible into the vacuum induction atomization furnace, cover the furnace door, and start evacuating until the vacuum reaches 5×10 -2 After Pa, the raw materials in the crucible are heated to 1400~1600 ℃ through the induction coil to melt, and the molten metal flows into the atomizing nozzle through the guide hole.
[0043] (3) Use argon gas at a pressure of 1-2 MPa at 800-1500 m 3 The flow rate of / h is through the atomizing nozzle to impact and break the molten metal falling into the atomization area, so that it is atomized into fine metal droplets, which are then cooled and solidified in the atomization chamber to form high entropy alloy powder. After screening, spherical Al2O3 with a particle size range of 15~53 μm is obtained. 22 Cr 30 Co 30 Ni 18 powder.
[0044] (4) Al was sprayed and deposited on the surface of TC4 titanium alloy substrate after sandblasting by using supersonic flame spraying technology. 22 Cr30 Co 30 Ni 18 The corresponding coating material can be obtained by high entropy alloy powder. The spraying process is oxygen flow rate 50.2 m 3 / h, kerosene flow rate 21.5 L / h, powder feeder speed 22 rpm, spray gun moving speed 800 mm / s, spraying distance 38.0 cm, pass spacing 2 mm, compressed air pressure 110 MPa, compressed air flow rate 19 m 3 / h, the coating thickness is about 400 μm.
[0045] (5) Phase structure and properties of high entropy alloy coating: The crystal structure is a single BCC phase, the nanohardness is 9.1 GPa, and the microhardness is 860 HV 0.1 The cumulative mass loss after cavitation in deionized water for 10 h is only 6.9 mg, showing the characteristics of typical ultra-high hardness and extremely excellent anti-cavitation performance.
[0046] Comparative Example 1 (1) A high entropy alloy powder (not within the atomic percentage range specified in the claims of the present invention) with a particle size range of 15-53 μm and an atomic percentage of Al 10%, Cr 28%, Co 28%, and Ni 34% prepared by vacuum induction atomization powder making technology is selected as a spray feed.
[0047] (2) Al was sprayed and deposited on the surface of the 316L stainless steel substrate after sandblasting by using supersonic flame spraying technology. 10 Cr 28 Co 28 Ni 34 The corresponding coating material can be obtained by high entropy alloy powder. The spraying process is oxygen flow rate 52.3 m 3 / h, kerosene flow rate 22.7 L / h, powder feeder speed 21 rpm, spray gun moving speed 600 mm / s, spraying distance 38.0 cm, pass spacing 2 mm, compressed air pressure 110 MPa, compressed air flow rate 19 m 3 / h, the coating thickness is about 500 μm.
[0048] (3) Al 10 Cr 28 Co 28 Ni 34 Phase structure and properties of high entropy alloy coating: The crystal structure is a single FCC phase, the nanohardness is 4.7 GPa, and the microhardness is 516 HV 0.1, the cumulative mass loss after cavitation in deionized water for 10 h is 11.2 mg, which shows that the hardness and cavitation resistance of the coating are worse than those of the coating of the present invention. This shows that although the type of metal components, powder particle size and spraying process are consistent with the present invention, as long as the atomic ratio of the metal components is not within the range specified in the claims of the present invention, it is impossible to prepare an ultra-high hardness cavitation-resistant high-entropy alloy coating.
[0049] Comparative Example 2 (1) A high entropy alloy powder (not within the range of component types and atomic percentages specified in the claims of the present invention) with a particle size range of 15-53 μm and an atomic percentage of Al 20%, Cr 20%, Co 20%, Fe 20% and Ni 20% prepared by vacuum induction atomization powder making technology is selected as a spray feed.
[0050] (2) The corresponding coating material can be obtained by spraying and depositing AlCrCoFeNi high entropy alloy powder on the surface of 316L stainless steel substrate after sandblasting roughening using supersonic flame spraying technology. The spraying process is oxygen flow rate 20.4 m 3 / h, natural gas flow rate 16.6 m 3 / h, powder feeding rate is 25 g / min, spray gun moving speed is 800 mm / s, spraying distance is 27.5 cm, pass spacing is 2 mm, compressed air pressure is 110 MPa, compressed air flow rate is 19 m 3 / h, the coating thickness is about 450 μm.
[0051] (3) Phase structure and properties of AlCrCoFeNi high entropy alloy coating: The crystal structure is a single BCC phase, the nanohardness is 7.7 GPa, and the microhardness is 705 HV 0.1 , the cumulative mass loss after cavitation in deionized water for 10 h is 20.1 mg, which shows that although the hardness of the coating is higher than that of Comparative Example 1, the cavitation resistance is worse. This shows that although the crystal structure of the coating is consistent with the present invention, as long as the type of metal components, atomic ratio and spraying parameters are not within the range specified in the claims of the present invention, it is impossible to prepare an ultra-high hardness cavitation-resistant high-entropy alloy coating.
[0052] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement modes and shall be included in the protection scope of the present invention.
Claims
1. A method for preparing an ultra-high hardness cavitation-resistant high-entropy alloy coating, characterized in that: The following steps are involved: (1) According to the atomic percentage of Al 20%~26%, Cr 30%~34%, Co 30%~34%, and Ni 16%~22%, prepare the corresponding mass of pure metal raw materials containing Al, Cr, Co, and Ni, clean the crucible at the same time, and then put the prepared raw materials into the crucible of the induction heating furnace; (2) Evacuate the air to ensure that the vacuum degree is ≤1×10 -1 Pa, the raw material is heated to 1250~1750℃ through an induction coil to melt and flow into the atomization zone, and the metal liquid is impacted and broken by high-speed and high-pressure inert gas to atomize it into fine metal droplets, which are then cooled and solidified into high-entropy alloy powder in the atomization chamber. After screening, the powder with a particle size range of 15~70 μm suitable for supersonic flame spraying technology is obtained; (3) The surface of the metal substrate is roughened by sandblasting and cleaned, and then fixed on a spraying table. After setting the spraying process parameters, the supersonic flame spraying equipment is started, and the powder obtained in step (2) is sent into the flame flow for spraying and deposition on the surface of the metal substrate to obtain an ultra-high hardness cavitation-resistant high-entropy alloy coating.
2. The method for preparing the ultra-high hardness cavitation-resistant high-entropy alloy coating according to claim 1, characterized in that: The purity of the pure metal raw materials of Al, Cr, Co and Ni in step (1) is above 99.9 wt.%.
3. The method for preparing a super-high hardness cavitation-resistant high-entropy alloy coating according to claim 1, characterized in that: In step (2), the inert gas is any one of nitrogen, argon and helium, the pressure of the inert gas is 0.5~5 MPa, and the flow rate of the inert gas is 900~1500 m 3 / h.
4. The method for preparing a super-high hardness cavitation-resistant high-entropy alloy coating according to claim 1, characterized in that: In step (3), the metal substrate is one of copper alloy, titanium alloy, aluminum alloy, stainless steel, nickel aluminum bronze, manganese aluminum bronze, aluminum bronze, L907A steel, and cast steel, and the roughness of the metal substrate surface after sandblasting is Ra≥1μm.
5. The method for preparing a super-high hardness cavitation-resistant high-entropy alloy coating according to claim 1, characterized in that: In step (3), the fuel gas used by the supersonic flame spraying equipment is natural gas, propane or aviation kerosene, the auxiliary fuel gas is oxygen or air, and the carrier gas is nitrogen, argon or helium.
6. The method for preparing a super-high hardness cavitation-resistant high-entropy alloy coating according to claim 1, characterized in that: The spraying parameters in step (3) are oxygen flow rate 50~56 m 3 / h, gas flow rate 20~25 L / h, powder feeder speed 20~25 rpm, spray gun moving speed 200~1000 mm / s, spraying distance 25~40 cm, stroke spacing 1~4 mm, compressed air pressure 100~120MPa, compressed air flow rate 18~22 m 3 / h.
7. The method for preparing a super-high hardness cavitation-resistant high-entropy alloy coating according to claim 1, characterized in that: The ultra-high hardness cavitation-resistant high-entropy alloy coating deposited in step (3) has a thickness of 100-800 μm, and the coating phase structure is a single BCC phase.
8. An ultra-high hardness cavitation-resistant high-entropy alloy coating prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-entropy alloy powder material for supersonic spraying and manufacturing method thereof
CN103056352A
Preparation method for cold spraying of high-entropy alloy coating on surface of magnesium alloy
CN113430513A
Cavitation-corrosion-resistant high-entropy alloy coating and preparation method thereof
CN115418595A
Laser-cladding high-hardness high-wear-resistance high-entropy alloy coating and preparation method thereof
CN115928066A
Alloy structure
JP2016023351A